2012
DOI: 10.4236/jmp.2012.310175
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Evidence for Revision of Fickian First Law and New Understanding of Diffusion Problems

Abstract: Based on the divergence theorem, we reveal that the Fickian first law relevant to the diffusion flux |<i>J(t,x,y,z) </i>> in the time and space is incomplete without an integral constant |<i>J<sub>0</sub>(t) </i>> for the integral of Fickian second law. The new diffusion flux (NDF) taking it into account shows that we can systematically understand the problems of one-way diffusion, impurity diffusion and self-diffusion as a special case of the interdiffusion. Applying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 9 publications
1
38
0
Order By: Relevance
“…As a result, we revealed that the diffusivity in (1) corresponds to the angular momentum operator L in quantum mechanics. The obtained new diffusivity will be useful for understanding of an elementary process of diffusion [3].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, we revealed that the diffusivity in (1) corresponds to the angular momentum operator L in quantum mechanics. The obtained new diffusivity will be useful for understanding of an elementary process of diffusion [3].…”
Section: Introductionmentioning
confidence: 99%
“…The Fickian second law is also obtained from the provability of differential equation [2]. In mathematics, the Fickian first law is obtained by integrating the Fickian second law with respect to nabla operator [3]. Therefore, it is considered that the Fickian law is only one, i.e., the Fickian second law.…”
Section: Introductionmentioning
confidence: 99%
“…The Gauss theorem reveals that the diffusion region space moves as shown in the relation between Equations (20) and (21). In other words, the discussion of coordinate transformation about the diffusion equations is indispensable for investigating the diffusion phenomena meaning the relative motion between micro particles.…”
Section: Mathematical Misconceptions In the History Of Diffusionmentioning
confidence: 99%
“…is mathematically valid because of ( ) { } eq 0 x J t J ∂ ∂ + = [21]. Here, it is consi-The definition of diffusivity relevant to a relative motion between micro particles indicates that the coordinate origin of diffusion equation should be usually set at a point in the diffusion region space.…”
mentioning
confidence: 99%